Understanding the emergence of the boson peak in molecular glasses - Mario González-Jiménez; Trent Barnard; Ben A. Russell; Nikita V. Tukachev; Uroš Javornik; Laure-Anne Hayes; Andrew J. Farrell; Sarah Guinane; Hans M. Senn; Andrew J. Smith; Martin Wilding; Gregor Mali; et al. (Nature Communications, 2023)
The ‘boson peak’ refers to an extra peak in the terahertz vibrational spectrum of glasses. It is now shown that for liquids of highly symmetric molecules the boson peak can be singled out by means of depolarized Raman scattering; the peak is linked to the formation of clusters of about 20 molecules.